The brain : the story of you - Eagleman, David (Pantheon Books, 2015)
"The dramatic story of the brain's role in creating our world, our experience of it, and ourselves; the basis for a PBS television series by the bestselling David Eagleman. How does a three pound mass of biological matter locked in the dark, silent fortress of the skull produce the extraordinary multi-sensory experience that comprises us, while also constructing reality and guiding us through the endless need to make decisions and determine our judgments and into a future that we are convinced we are shaping? David Eagleman compares the brain to a cityscape with different neighborhoods where neural networks vie for supremacy and determine our behavior in ways we are not always aware or in control of. At the same time, he suggests that the brain works as a storyteller--creating a narrative that allows us to navigate and make sense of a world that it is busy constructing for us"--